2000
DOI: 10.1093/toxsci/58.1.161
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of [Ring-U-14C]styrene in Rats and Mice Exposed by Recirculating Nose-Only Inhalation

Abstract: The disposition of styrene was studied in a group of 12 Sprague Dawley rats and two groups of 30 CD1 mice exposed separately to 160 ppm [ring-U-(14)C]styrene of high specific radioactivity of 1.92 TBq x mol(-1) (52 Ci x mol(-1)) for 6 h. A nose-only exposure system was successfully adapted to (1) recirculate a portion of the flow to limit the amount of (14)C-styrene required, and (2) avoid any polymerization of the compound. The mean uptake of styrene in rats was 113 +/- 7 micromol x kg(-1) x h(-1) and stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…No evidence of DNA adduct formation was measured in either the mouse or rat lung samples at a limit of detection of 3 and 5 adduct/10 7 nucleotides for the -and -isomers, respectively. Other studies including Boogaard et al (2000) and Otteneder et al (2002) have also indicated that mouse lung tumor formation is not associated with DNA adduct formation. Moreover, styrene did not cause mutations when tested in vivo (Speit and Henderson, 2005).…”
Section: Introductionmentioning
confidence: 93%
“…No evidence of DNA adduct formation was measured in either the mouse or rat lung samples at a limit of detection of 3 and 5 adduct/10 7 nucleotides for the -and -isomers, respectively. Other studies including Boogaard et al (2000) and Otteneder et al (2002) have also indicated that mouse lung tumor formation is not associated with DNA adduct formation. Moreover, styrene did not cause mutations when tested in vivo (Speit and Henderson, 2005).…”
Section: Introductionmentioning
confidence: 93%
“…The disadvantage with these systems is a large deposition of the aerosolized drug all over the animal's Alternatively, nose-only inhalation chambers were developed to avoid the above problems for small animals like rats and mice. 23,24 Validation of these nose-only inhalation chambers is an important step towards their suitable use in inhalation studies. 25,26 Unfortunately, little data is available in the literature on the fraction of drug that deposits in the mice and their lungs using such chambers.…”
Section: 11mentioning
confidence: 99%
“…4-VP is a more potent toxicant in mice than either styrene or SO. Approximately 95% of the styrene retained upon inhalation was excreted as urinary metabolites by rats 12) .…”
mentioning
confidence: 99%